EXPLORING THE FUNCTIONS OF CODE SWITCHING IN THE CONTEXT OF TEACHING AND LEARNING ACTIVITIES - Putu Ayu Suryaningsih (Jurnal IKA, 2023)
Indonesian society can be said as a bilingual and multilingual society. They are able to use two or more languages ​ in communicating, such as local language, national language, and even foreign language. The ability to use two or more languages ​​allows them to switch from one language to another while communicating. In sociolinguistics, the phenomenon of language switching is known as code-switching. The aim of this research was to determine the functions of code-switching in teaching and learning activities. This study used library research data collection techniques. This qualitative research was conducted by recording and collecting data and information from library sources, such as books and articles related to the topic of this research. The results of this study showed that there are various codes switching functions that occur in education field, which is in teaching and learning activities. In general, code switching carried out in teaching and learning activities had an academic function. Code switching was carried out in teaching and learning activities to avoid misunderstanding and misinterpretation in delivering and receiving subject matter